Exploring EFL Teachers Perspectives on Collaborative Learning Activities in Senior High School Contexts - Wijaya, Kristian Florensio (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2021)
Abstract In this global age, it is of critical importance for future workforces to possess both higher intellectual and social competencies crucially sustaining their careers. In accord with this fact, second language educators engaging in worldwide second language learning circumstances have taken a critical stance to promote collaborative learning activities earlier in senior high school contexts to maximize these future generations’ potentials in terms of problem-solving, critical thinking, social, and conflict resolution skills. This was a qualitative study conducted in a narrative way to decipher the observed recurring phenomenon accurately based on people’s stories and experiences. Open-ended interviews were also utilized in this study to obtain more natural and authentic portrayals regarding the stories told by participants. 2 EFL teachers having different expertise and experiences in running collaborative learning activities in distinctive Senior High School Contexts were also involved in this study to yield richer and reliable results out of the data gathered. The study revealed that collaborative learning activities will run more efficiently when supportive learning assistances are extensively addressed and a higher degree of reverence occurred among diverse group members. Keywords: EFL Teachers’ Perspectives, Collaborative Learning Activities, Senior High School Contexts